Manual pollination of non-self-pollinating Arbequina olive trees using three pollen-donor cultivars - Gobi, Samuel Francisco; Gottinari Kohn, Rosete Aparecida; Moreno Kirinus, Marines Batalha; Barbosa Malgarim, Marcelo; Brasil Costa, Vagner (Pesquisa Agropecuaria Brasileira, 2025)
The objective of this work was to evaluate how the productivity of the non-self-pollinating olive cultivar Arbequina is affected by manual pollination with pollen from cultivars Coratina, Pendolino, and Koroneiki in Brazil. The study was conducted over two crop years, and the donor cultivars were chosen due the proximity of their flowering periods. The inflorescences were bagged during the pre-flowering stage, and an in vitro germination test was subsequently conducted to verify the viability of the pollen grains. The first pollen application occurred on the third day after the anthesis of the donor cultivars, and the second, seven days later. Afterwards, production analyses were conducted. In both study years, 'Coratina' stood out as a pollen donor compared with 'Arbequina' (self-pollinated control) regarding the parameters number of viable fruits (2.38 and 4.30% vs. 0.5 and 0.42%), production per plant (23.05 and 41.64 kg per plant vs. 4.84 and 4.06 kg per plant), and productivity (6,569.25 and 11,868.54 kg ha-1 vs. 1,379.97 and 1,159.09 kg ha-1). The pollination of 'Arbequina' with pollen from 'Coratina' increases the number of viable fruits and, consequently, favors crop productivity.